2011
DOI: 10.1111/j.1468-0297.2011.02433.x
|View full text |Cite
|
Sign up to set email alerts
|

Service Regulation and Growth: Evidence from OECD Countries

Abstract: We study the effects of anti-competitive service regulation by examining whether OECD countries with less anti-competitive regulation see better economic performance in manufacturing industries that use less-regulated services more intensively. Our results indicate that lower service regulation increases value added, productivity and export growth in downstream service-intensive industries. The regulation of professional services and energy provision has particularly strong negative growth effects. Our estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
149
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(156 citation statements)
references
References 33 publications
2
149
1
Order By: Relevance
“…When we compute the marginal effect of deregulation on industry production we find that, for low transport intensity sectors (25th percentile), a unit decrease in the entry barriers index is associated with a one for all 0.6% increase in gross output; in turn, for high transport intensity sectors (75th percentile), the effect on production is about 1.9%. 23 Barone and Cingano (2008) and Arnold et al (2008a,b)) found a positive impact of deregulation in service sectors (transports, electricity and telecommunication) on the productivity of downstream industries which use the liberalized services more intensively as an intermediate input.…”
Section: Robustness Analysismentioning
confidence: 90%
See 2 more Smart Citations
“…When we compute the marginal effect of deregulation on industry production we find that, for low transport intensity sectors (25th percentile), a unit decrease in the entry barriers index is associated with a one for all 0.6% increase in gross output; in turn, for high transport intensity sectors (75th percentile), the effect on production is about 1.9%. 23 Barone and Cingano (2008) and Arnold et al (2008a,b)) found a positive impact of deregulation in service sectors (transports, electricity and telecommunication) on the productivity of downstream industries which use the liberalized services more intensively as an intermediate input.…”
Section: Robustness Analysismentioning
confidence: 90%
“…This latter approach is related to the seminal paper by Rajan and Zingales (1998) who argued that the impact of cheaper external finance on productivity growth should be stronger in those sectors that rely more extensively on external finance. A similar approach is adopted by Barone and Cingano (2008) who examine whether OECD countries with less anti-competitive regulation in service sectors show a better economic performance of manufacturing industries that use less regulated services more intensively.…”
Section: Model Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Countries with more competitive regulatory frameworks for services achieve higher added value, productivity and export growth in the manufacturing sectors that use services as inputs more intensively (Barone and Cingano, 2011). The potential beneficial effects are particularly strong for Spain, which is one of the OECD countries whose manufacturing exports embody higher value added from services (OECD, 2013d).…”
Section: Strengthening Competition and Boosting Cost Competitivenessmentioning
confidence: 99%
“…Regulatory reforms that imply a reduction in entry barriers, in the markup of prices over costs and in adjustment costs tend to increase investment Alesina (2005). Recently, Barone and Cingano (2011) find that lower service regulation has non-negligible positive effects on the value added, productivity and export growth rates of serviceintensive users. For a survey of the literature on regulation and economic performance see Rincon-Aznar et al (2010) and Arnold et al (2011). variables and country-level financial variables, such as the size of capital markets, or measures of financial efficiency and financial development ECB (2013).…”
mentioning
confidence: 98%